Single port laparoscopic mesh rectopexy - Ahmed, Ghada Morshed (Gastroenterology Review/Przegląd Gastroenterologiczny, 2016)
Introduction : Traditionally, laparoscopic mesh rectopexy is performed with four ports, in an attempt to improve cosmetic results. Following laparoscopic mesh rectopexy there is a new operative technique called single-port laparoscopic mesh rectopexy. Aim : To evaluate the single-port laparoscopic mesh rectopexy technique in control of rectal prolapse and the cosmesis and body image issues of this technique. Material and methods : The study was conducted in El Fayoum University Hospital between July 2013 and November 2014 in elective surgery for symptomatic rectal prolapse with single-port laparoscopic mesh rectopexy on 10 patients. Results : The study included 10 patients: 3 (30%) males and 7 (70%) females. Their ages ranged between 19 years and 60 years (mean: 40.3 ±6 years), and they all underwent laparoscopic mesh rectopexy. There were no conversions to open technique, nor injuries to the rectum or bowel, and there were no mortalities. Mean operative time was 120 min (range: 90–150 min), and mean hospital stay was 2 days (range: 1–3 days). Preoperatively, incontinence was seen in 5 (50%) patients and constipation in 4 (40%). Postoperatively, improvement in these symptoms was seen in 3 (60%) patients for incontinence and in 3 (75%) for constipation. Follow-up was done for 6 months and no recurrence was found with better cosmetic appearance for all patients. Conclusions : Single-port laparoscopic mesh rectopexy is a safe procedure with good results as regards operative time, improvement in bowel function, morbidity, cost, and recurrence, and with better cosmetic appearance.